2021
DOI: 10.3233/jpd-212687
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of the Timed Up and Go Test in Subjects with Parkinson’s Disease: Implications for Longitudinal Assessments

Abstract: Background: Despite the frequent use of the Timed Up and Go (TUG) test in clinical trials, evaluation of longitudinal test-retest reliability is generally lacking and still inconclusive for patients with Parkinson’s disease (PD). Objective: We aimed to further investigate long-term reliability and sensitivity of the TUG test among this population. Furthermore, we explored alternative assessment strategies of the test aimed at elucidating whether the inclusion or combination of timed trials may have potential i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Furthermore, we observed a significant reduction in TUG scores only within the Biodanza group compared to the baseline assessment, with repercussions in terms of greater postural stability and a reduction in the risk of falling. The improvements recorded in TUG times at the end of active treatment have been reported also in previous studies that adopted other types of dance therapy, despite this measure seems to be less sensitive to the intervention effects than the other measures of functional mobility [ 28 , 49 , 50 ]. Hackney and Earhart also demonstrated that complex tango steps produced improvement effects in terms of balance and postural stability [ 51 ].…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, we observed a significant reduction in TUG scores only within the Biodanza group compared to the baseline assessment, with repercussions in terms of greater postural stability and a reduction in the risk of falling. The improvements recorded in TUG times at the end of active treatment have been reported also in previous studies that adopted other types of dance therapy, despite this measure seems to be less sensitive to the intervention effects than the other measures of functional mobility [ 28 , 49 , 50 ]. Hackney and Earhart also demonstrated that complex tango steps produced improvement effects in terms of balance and postural stability [ 51 ].…”
Section: Discussionsupporting
confidence: 73%
“…The Timed Up and Go (TUG) test [ 35 ] is a useful tool to assess gait-related functioning and motor symptoms because it involves sequential locomotor tasks that incorporate walking and turning, which are both affected by cognitive impairment [ 36 , 37 ]. In the assessment protocol, patients were seated on a chair, and were instructed to stand up, walk at their own comfortable and safe walking speed for 3 m, turn 180◦ at a designated spot, come back, and sit down on the chair again.…”
Section: Methodsmentioning
confidence: 99%
“…This test was initially developed by Podsiadlo and Richardson in 1991 [1] in the original version of the test named the "Get-up and Go", which aimed to evaluate dynamic balance in elderly people [2]. This test was further successfully tested on patients with multiple disorders [3][4][5]. The TUG test highly correlates with age, socioeconomic status, and multiple comorbidities [6].…”
Section: Introductionmentioning
confidence: 99%